Kenya Climate-Smart Agriculture Framework Program - Ministry of Agriculture, Livestock and Fisheries, Kenya; Ministry of Environment and Natural Resources (2015)
Kenya envisions being a middle- income country with citizens enjoying high quality of life and a sustained annual economic growth rate of at least 10% by the year 2030 according to the National Development Blue Print “The Kenya Vision 2030”. The agriculture sector has been identified as one of the key sectors to contribute to the projected annual national economic growth.